AI SIMULATORS FOR ENHANCING ANATOMICAL KNOWLEDGE IN MEDICAL PRACTICE - Bakiyeva Muhabbat; Dildora Doniyorova (Modern American Journals, 2025)
Recent advances in artificial intelligence (AI) have transformed medical education by providing innovative tools for interactive learning. Among these, AI-based simulators play a critical role in strengthening anatomical knowledge and clinical skills among medical students and practitioners. These simulators offer three-dimensional (3D) visualizations of the human body, allowing users to explore anatomical structures with high accuracy and repeatability. They also support real-time feedback, adaptive learning, and virtual dissection, which enhance understanding without the ethical and logistical limitations associated with cadaveric training. This paper explores the development, application, and effectiveness of AI simulators in anatomy education and their role in improving medical practice outcomes. The integration of AI-driven technologies not only enriches the learning process but also prepares future healthcare professionals for precision medicine and digital healthcare systems.
Keywords: Artificial intelligence; anatomy education; medical simulation; virtual dissection; 3D visualization; adaptive learning; digital healthcare.